2015
DOI: 10.1080/21688370.2015.1037418
|View full text |Cite
|
Sign up to set email alerts
|

Capillary collagen as the physical transport barrier in drug delivery to tumor microenvironment

Abstract: The capillary wall is among the most important barriers that controls mass exchange between tumor microenvironment and systemic circulation. There are numerous studies on endothelial cells role in this mass exchange, but the role of capillary collagen of Type-IV in transport of small molecules and nanotherapeutics is less known. Our recent study revealed that the capillary wall collagen modulates the drug transport across the wall, and that it can be taken as a biophysical marker for drug transport. In our in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Other studies imaging the distribution of iv-injected trastuzumab and cetuximab in HER2 and EGFR-positive tumors revealed a poor and heterogeneous distribution of therapeutics in the TME due to the limited convection and diffusion [ 33 , 34 ]. These data are in accord with our previous studies showing limited access of the circulating nanotherapeutics to tumor cells due to the various biophysical barriers in the TME [ 35 , 36 , 37 ]. Indeed, in our current study, the IVM images revealed a limited distribution of iv injected fluorescently labeled anti-PD-L1 IgG preferentially at the border, but not deep inside the tumor 6 h after the injection, while PD-L1 is expressed by the entire tumor.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies imaging the distribution of iv-injected trastuzumab and cetuximab in HER2 and EGFR-positive tumors revealed a poor and heterogeneous distribution of therapeutics in the TME due to the limited convection and diffusion [ 33 , 34 ]. These data are in accord with our previous studies showing limited access of the circulating nanotherapeutics to tumor cells due to the various biophysical barriers in the TME [ 35 , 36 , 37 ]. Indeed, in our current study, the IVM images revealed a limited distribution of iv injected fluorescently labeled anti-PD-L1 IgG preferentially at the border, but not deep inside the tumor 6 h after the injection, while PD-L1 is expressed by the entire tumor.…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported that free DOX concentrations inside the subcutaneous 4 T1 tumor increased and then rapidly diminished within 24 hours after the i.v. injection which was very similar to that reported by other group [36], [38]. In the current study, we also evaluated kinetics of free doxorubicin inside liver metastases as small molecule chemotherapeutics may be less subjective to reduced vascular permeability inside tumors.…”
Section: Discussionsupporting
confidence: 82%
“…We also estimated the vascular permeability of tumor-associated blood vessels, which is also a major biophysical barrier for drug delivery [36], [37]. Drugs that pass through the capillary endothelial cell layer first encounter the basal membrane, in which major constituent is type IV collagen [13], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Man-MPs efficiently degrade tumor collagen. Tumor ECM, consisting of a collagen network and proteoglycans, provides a natural barrier against monocyte infiltration and therapeutic drug accumulation and penetration, resulting in the immune evasion and resistance of antitumor therapy 48 . Similar to RAW264.7 macrophages, MPs and Man-MPs derived from RAW264.7 macrophages overexpressed MMP9 and MMP14 proteins (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%